2015
DOI: 10.1007/s11845-015-1319-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrating HIV and addiction care for non-engaging HIV-infected opiate-dependent patients

Abstract: Integration of HIV and addiction care optimises the physical health of non-engaging HIV-positive opiate-dependent patients with no substantial effect on their methadone maintenance programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Integration of HIV and methadone treatment services has been shown to improve immunologic function in people who use drugs (Kinahan et al, 2015). The high failure rate to initiate ART among people who inject drugs in resource-limited settings represents a lost opportunity to reduce morbidity, mortality and the spread of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of HIV and methadone treatment services has been shown to improve immunologic function in people who use drugs (Kinahan et al, 2015). The high failure rate to initiate ART among people who inject drugs in resource-limited settings represents a lost opportunity to reduce morbidity, mortality and the spread of infection.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies took place in North America (n=15 in the United States and n=1 in Canada), four took place in Europe [53,54,60,68] and three took place in Asia [52,59,74]. Half of studies had a follow-up period of 12 months or longer ( Table 1).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…In two randomized trials, HIV testing and counseling alone in opioid treatment settings led to increased HIV testing performed and feedback of results [55,75], but the addition of sexual risk-reduction counseling did not lead to significant changes in sexual risk behaviors [69]. ART management in opioid treatment settings involved the prescription of ART in methadone clinics [68] or directly-administered ART (DAART) [53,56,60,[64][65][66]70]. DAART in residential opioid treatment settings [53] and methadone clinics was safe and feasible [56,60,[64][65][66]70], but a randomized trial demonstrated that DAART compared with self-administered ART in methadone clinics did not lead to significant differences in clinical outcomes [63].…”
Section: Interventions In Opioid Treatment Settingsmentioning
confidence: 99%
“…This serves as a basis for future model development to answer the WHO call to reach key populations with integrated HIV services using a combination approach that includes harm reduction services [1,2]. Other clinics have successfully integrated HIV care and opioid treatment programs, but this is the first time, to our knowledge, that it is being reported in sub-Saharan Africa [21,39,40]. IMAT adds to the body of literature showing that integration of HIV care for PWUD is an effective approach to ensuring their timely and appropriate care and treatment [41,42,43].…”
Section: Discussionmentioning
confidence: 99%